A review on kinetic parameters in scoliotic patients - Mohammad Taghi Karimi; Azadeh Nadi (Vesnu Publications, 2013)
Introduction: Scoliosis is a common deformity of spinal column. Most previous researches have concentrated mainly on kinematic parameters. However, this spinal abnormality is also a structural deformity affects on the normally symmetrical vertebral column, alters the centre of mass position, and weight distribution on the lower limbs. Therefore, kinetic evaluation can lead to a better understanding of the etiology of scoliosis. The aim of this study was to evaluate kinetic parameters in scoliotic subjects and compare with normal participants considering previous studies. Materials and Methods: In this research, some key words like scoliosis, kinetic, ground reaction force, center of pressure, moment, and intervertebral force were used to find suitable articles. These researches were found on data bases such as Google Scholar, PubMed, Elsevier, Ovid, and Springer. Papers were selected based on identified inclusion and exclusion criteria. Then articles were scored by downs and black tool. Results: Among thirteen articles, eleven were selected from 1998 to 2012. For symmetric index, researchers indicated an asymmetry, but these asymmetries did not follow any special pattern with curves. Also, researchers showed that maximum displacement in center of pressure occurred on mediolateral direction. Another article investigated kinetic parameters evaluation during lateral steps, because in this gait pattern asymmetries were greater between two normal and patient groups. Conclusion: According to previous studies, there was an asymmetry in parameters. But, there is not any relationship between asymmetry and curves pattern in scoliotic subjects. Keywords: Scoliosis, Gait, Kinetic